2020
DOI: 10.18357/bigr12202019599
|View full text |Cite
|
Sign up to set email alerts
|

The Schengen Crisis and the End of the “Myth” of Europe Without Borders

Abstract: The European Schengen crisis, spurred off by a wave of terrorist attacks in Europe and an unexpected increase in migration across the Mediterranean Sea in 2015 led to a re-questioning of the functions of borders in European integration. The ideal of a “Europe without borders” has been particularly affected. Indeed, the re-introduction of border controls in several Member States of the European Union (EU) symbolized a new obstacle to free circulation in Europe and the “separation” function of the border seems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…It was the 2015 refugee crisis, however, which led to a questioning of both the functions of borders in controlling migration, as well as European integration as a whole. The ideal of a "Europe without borders" was questioned because both the Schengen agreement and the Dublin convention were unable to deal with this crisis (Brunet-Jailly and Wassenberg, 2020). According to studies of the French-Italian border, the impact of the 2015-crisis related border checks on inhabitants of this region was rather symbolic than factual, as the checks concentrated on thirdcountry nationals and left the majority of border crossings unaffected (Casella Colombeau, 2020).…”
Section: Researching Re-borderingmentioning
confidence: 99%
See 2 more Smart Citations
“…It was the 2015 refugee crisis, however, which led to a questioning of both the functions of borders in controlling migration, as well as European integration as a whole. The ideal of a "Europe without borders" was questioned because both the Schengen agreement and the Dublin convention were unable to deal with this crisis (Brunet-Jailly and Wassenberg, 2020). According to studies of the French-Italian border, the impact of the 2015-crisis related border checks on inhabitants of this region was rather symbolic than factual, as the checks concentrated on thirdcountry nationals and left the majority of border crossings unaffected (Casella Colombeau, 2020).…”
Section: Researching Re-borderingmentioning
confidence: 99%
“…A substantial part of Europeans (used to) cross national borders on a daily or weekly basis for education, work or leisure (ESPON, 2018;Jaansoo, 2019) and contributed thus to de-territorialism (Medeiros et al, 2020). The decreasing importance of national borders, studied as debordering, created a mainstream of border scholarship (Brunet-Jailly and Wassenberg, 2020). This story started to be harpooned by growing Euroscepticism, which had Brexit as its main consequence so far (Riedel, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, it turned out that on the twenty-fifth anniversary of the Schengen agreement, almost all movement within its area was prohibited. The trend towards erecting barriers to the movement of individuals, which had emerged a few years earlier to limit migration flows that had swept the EU countries, reached its climax (Filippov 2020;Wassenberg 2020). The closure of the borders took place in an atmosphere of extreme alarm and haste, asynchronously and asymmetrically, and it was not agreed even between the EU countries.…”
Section: Socio-territorial Consequences Of the Pandemicmentioning
confidence: 99%
“…The pandemic showed that Europe was not immune to this phenomenon. As the last decade has shown signs of a hardening of European borders especially in the context of the wave of terrorist attacks that flared up across Europe-especially in France in 2015-2016-and of the so-called migrant "crisis" that started in 2015 (Bartel, Delcroix, and Pape 2020;UNHCR 2020;Wassenberg 2020), this trend of chronic reinforcements of borders within the Schengen Area has persisted and expanded. The COVID-19 pandemic temporarily put on hold the Schengen Area insofar as all countries closed their borders.…”
Section: Lockdown Complicates Lives Of Border Residentsmentioning
confidence: 99%